STRESS AND ITS RELATIONSHIP WITH SELECTED FACTORS AMONG WOMEN - Pais, Maria; Noronhna, Judith A; K., Pavan Bhat (Journal of Health and Allied Sciences NU, 2015)
Introduction: Stress is a complex, dynamic process of interaction between a person and his or her life. It is the war one reacts physically, mentally and emotionally to the various conditions. The purpose of the present study was to investigate stress, its relationships with selected factors among women.Study Design: A descriptive survey design was used to identify the stress and its relationship with selected factors among (200) women aged 18-45 years.Results: The present study reveals that level of stress was high among unmarried women (85%) when compared to married women (76%). The present study also revealed that there was a significant association between stress and age, age at menarche, education, BMI and dysmenorrhea among the married and unmarried women.Conclusions: Stress was more prevalent among unmarried women, age, educational status, age at menarche; BMI and dysmenorrhea were strongly associated with stress.
Keywords: Stress; Married and unmarried women; conceptual frame work